Helicobacter pylori induces gastric cancer via down‐regulating miR‐375 to inhibit dendritic cell maturation. Issue 4 (3rd May 2021) - Zhang, Zhenxing; Chen, Simiao; Fan, Menghui; Ruan, Guojing; Xi, Tao; Zheng, Lufeng; Guo, Le; Ye, Feng; Xing, Yingying
Abstract: Background: Recent studies and clinical samples have demonstrated that Helicobacter pylori could induce the downregulation of miR‐375 in the stomach and promote gastric carcinogenesis. However, whether the immune cells are affected by Helicobacter pylori due to the downregulation of miR‐375 is unclear. Materials and methods: In this study, we constructed an overexpression and knockdown of miR‐375 and Helicobacter pylori infection cell models in vitro. In addition, the maturity of dendritic cells (DCs) and the expression of IL‐6, IL‐10, and VEGF at the transcriptional and translational levels were analyzed. Changes in the JAK2‐STAT3 signaling pathway were detected. In vivo, the number changes in CD4+ T and CD8+ T cells and the size changes of tumors via models of transplantable subcutaneous tumors were also analyzed. Results: A cell model of Helicobacter pylori and gastric cancer was used to identify the expression of miR‐375 and the maturity of dendritic cells. This study found that Helicobacter pylori could downregulate miR‐375, which regulates the expression of cytokines IL‐6, IL‐10, and VEGF in the stomach. MiR‐375 regulated the expression of cytokines IL‐6, IL‐10, and VEGF through the JAK2‐STAT3 signaling pathway in vitro. In addition, we found that Helicobacter pylori regulates the maturation of dendritic cells through miR‐375. These results were further verified in vivo, and miR‐375 diminishes tumor size was also demonstrated. This study showed that immature DCs caused a decrease in the number of CD4+ and CD8+ T cells. Conclusions: This study demonstrated that Helicobacter pylori can inhibit miRNA‐375 expression in the stomach. Downregulated miR‐375 activates the JAK2‐STAT3 pathway. Activating the JAK2‐STAT3 signaling pathway promotes the secretion of IL‐6, IL‐10, and VEGF, leading to immature differentiation of DCs and induction of gastric cancer.